Delayed post gastrectomy haematuria: A rare distant site of signet ring cell carcinoma metastasis - Kamarulzaman, Mohd Nazli; Che Mohamed, Siti Kamariah; Johan Tambu, Rohan Malek (Bangladesh Journals OnLine(BanglaJOL), 2016)
Secondary bladder tumour is rare and most of the cases were direct extension of local tumour. Distant tumour metastasis to the bladder is extremely rare. We report a case of isolated bladder metastasis from gastric cancer after 2 years of sub-total gastrectomy. The patient presented with gross haematuria and bladder growth was noted during diagnostic cystoscopy. Transurethral resection of bladder tumour was performed and histopathology result confirmed the diagnosis of metastatic signet ring cell carcinoma which is a similar subtype with the previous cancer in the stomach. Radiological investigation confirmed the presence of bladder mass, but no peritoneal dissemination was shown on the imaging. Thus, this particular presentation of isolated bladder metastasis without peritoneal seedling was extremely rare.